2020
DOI: 10.1007/s10286-020-00683-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic effects of electronic cigarette use: a systematic review

Abstract: Purpose Electronic cigarettes (ECs) are the fastest growing tobacco product in the USA, and ECs, like tobacco cigarettes (TCs), have effects on the cardiovascular autonomic nervous system, with clinical implications. The purpose of this review was to collect and synthesize available studies that have investigated the autonomic cardiovascular effects of EC use in humans. Special attention is paid to the acute and chronic effects of ECs, the relative contributions of the nicotine versus non-nicotine constituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 53 publications
2
39
0
2
Order By: Relevance
“…Although it is reassuring that acute EC vaping did not acutely impair FMD, it would be dangerous and premature to conclude that ECs do not lead to atherosclerosis. However, there is increasing scientific literature (13,14,21) that supports the notion that ECs, although not harmless, may be less harmful than TC smoking for cardiovascular risk.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Although it is reassuring that acute EC vaping did not acutely impair FMD, it would be dangerous and premature to conclude that ECs do not lead to atherosclerosis. However, there is increasing scientific literature (13,14,21) that supports the notion that ECs, although not harmless, may be less harmful than TC smoking for cardiovascular risk.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Garcia and colleagues performed a systematic review and meta-analysis on the effects of EVC on blood pressure (BP), heart rate (HR), and heart rate variability (HRV), pooling data from 19 studies, and using largely explicit and valid methods [23]. They concluded that EVC are associated with acute increases in systolic blood pressure (SBP), diastolic blood pressure (DBP), and HR, and changes in HRV typical of sympathetic prevalence over vagal activity, even if mostly explained by nicotine exposure.…”
Section: Recent Findingsmentioning
confidence: 99%
“…Tobacco cigarette smoking is recognized as the most important modifiable risk factor for cardiovascular disease and it exerts its adverse events, at least partly, through an increase in sympathetic nerve activity [ 18 ]. In healthy smokers, smoking of the first TC of the day triggered a significant acute increase in systolic blood pressure by 7%, in diastolic blood pressure by 10%, and in the heart rate by 25% [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Electronic cigarette vaping also seems to produce acute cardiovascular effects. A meta-analysis compared the acute TCs and ECs cardiovascular effects and found that EC vaping resulted in an acute increase in the heart rate and systemic blood pressure, but to a lesser extent than TC smoking [ 18 ]. The authors attributed the sympathoexcitatory effects of ECs to the nicotine contained in the EC aerosol [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation